Mineralization of Nitrogen in Soils with Application of Acid Whey at Different pH - Braos, Lucas Boscov [UNESP] (2020)
Agro-industrial wastes are commonly used as nitrogen sources in agriculture, and its availability depends on the dynamics of nitrogen mineralization. The pH has great effects on soil nitrogen dynamics; thus, we hypothesized that the increase of pH would increase nitrogen mineralization and nitrification. The aim of this study was to evaluate the effects of pH and application of acid whey in nitrogen mineralization and nitrification rates using two types of soils, a hapludult and a eutrudox. In a completely randomized factorial design, N mineralization under different pH levels (4.5; 5.0; 5.5; 6.0; 6.5) was evaluated, with and without whey application, with an equivalent of 40 mg N dm−3. Soils were incubated for 182 days, and throughout this period, eleven evaluations were made to assess N mineralization over time. The hapludult soil had higher nitrate concentrations and the acid whey fertilization increased inorganic nitrogen in both soils. Soil pH did not influence inorganic nitrogen contents, but affected nitrification in both soils. Soil pH levels also resulted in variations on the constant of mineralization, a parameter related to mineralization speed, but without any strong trend. The application of acid whey displayed a satisfactory potential in relation to nitrogen incorporation in both tested soils. Soil pH around 4.5–5.5 is the optimum pH range, because it did not affect the nitrogen supply and decreases nitrification. Results demonstrate that soil pH can be used to avoid nitrification without reducing nitrogen availability to plants.